İdari para cezaları - Karakoç, Zeynep (My University, 2010)
Hayatın her alanında gelişim ve değişimin son derece hızlı yaşandığı günümüzde, hukuk normları toplumsal hayatı belli sınırlar çizerek güvence altına almak işlevinin çok ötesine geçmiştir. Bu nedenle de yasama, yürütme ve yargı fonksiyonları arasındaki etkileşim artmış, klasik anlamlarından sıyrılarak birbirlerinin yetki ve görevlerini üstlenir, hatta çoğu zaman birbirlerinin yerine geçer olmuştur. İdarenin ortada bir yargı kararı bulunmaksızın, yasaların açıkça verdiği yetki kapsamında idare hukuku ilkeleri doğrultusunda kurduğu bir idari işlem ile uyguladığı zorlama olarak karşımıza çıkan idarî yaptırımlar, özel olarak da idari para cezaları anılan etkileşim nedeniyle yaygınlaşmakta ve günlük yaşamın her alanında var olmaktadır. İlgili yasal düzenlemelerde dağınık biçimde yer alan idari para cezaları ve pek çok yasada suç sayılan fiillerin cezaları 4854 sayılı Bazı Kanunlardaki Cezaların İdari Para Cezasına Dönüştürülmesine Dair Kanun ile idari para cezasına dönüştürülmüştür. Sonrasında 5237 sayılı Türk Ceza Kanunu ile cürüm ve kabahat ayrımı kaldırılmıştır. Burada kabahatler yasa kapsamına alınmamış, 5326 sayılı Kabahatler Kanunu kapsamında düzenlenmiştir. İdari ceza hukuku adını verebileceğimiz, idarenin kolluk faaliyetinde temelini bulan idari yaptırımlarla ilgilenen yeni bir hukuk dalının oluştuğu görülmektedir. 5326 sayılı Kabahatler Kanunu idari para cezalarının yargısal denetimi görevini adli yargı düzenine bırakmış olmakla birlikte, idari rejimini benimseyen hukuk sistemimizde idari para cezalarının yargısal denetimi kural olarak idari yargı düzeninin görev alanında olmalıdır. Bu çalışmanın giriş kısmında yaptırım kavramı üzerinde durulmuş, birinci bölümünde idari para cezalarının tanımı, idari para cezalarına hakim olan ilkeler, 4854 ve 5326 sayılı yasalar ile getirilen düzenlemeler ve kurumlar belirtilmeye çalışılmıştır. İkinci bölümünde ise, idari para cezalarının yargısal denetimi konunda açıklamalara yer verilmiştir.

Today, when the developments and changes in all areas of life are lived extremely fast, legal norms have gone much further than their function of securing social life by drawing certain limits. Therefore, the interaction between legislation, execution and exercise of jurisdiction functions have increased, and by retrieving from their classical meanings, they have assumed each other’s authorization and duties, and they even started replacing each other. Legal sanctions that appear as enforcement implemented with an administrative process with respect to the principles of administration law, within the scope of the authorization given clearly with the laws, without the existence of a decree, especially administrative fines is becoming widespread due to the interaction mentioned and exists in all areas of our daily life. Administrative fines that are included in a scattered way in the relevant legal regulations, and the penalties of actions that are considered as crime in many laws, are turned into administrative fines with the Law on Converting Some Penalties into Fines in some Certain Laws with number 4854. Later on, the separation of criminal offense and misdemeanor was removed with the Turkish Criminal Law with number 5237. Here the misdemeanors were not included in the scope of law, and are regulated within the scope of Law on Misdemeanors, number 5326. It is seen that a new branch of law is formed that is interested in administrative sanctions, that finds its basis in the law-enforcement activities of the administration and which we can call administrative criminal law. Even though the Law on Misdemeanors, number 5326, have left the duty of supervision of the administrative fines to the order of ordinary courts, the judicial observation of administrative fines in our legal system that adopts the administrative regime, must be included in the duty area of the administrative judgment order. In the introduction section of this work, the concept of sanctions were emphasized and in section one, the definitions of administrative fines, principles that dominate the administrative fines, the regulations brought on by laws with numbers 4854 and 5326 and organizations were tried and stated. In section two, explanations on the subject of judicial observation of the administrative fines are included.
Keywords: Hukuk; Kamu Hukuku; Para Cezaları